Analisis Penerapan Marketing Mix Syariah Dalam Akad Rahn Tasjily Untuk Meningkatkan Jumlah Anggota Baitul Maal Wat Tamwil (Studi Kasus di BMT UGT Nusantara Cabang Pembantu Kencong): Analysis of the Implementation of Sharia Marketing Mix in Rahn Tasjily Contracts to Increase the Number of Baitul Maal Wat Tamwil Members (Case Study at BMT UGT Nusantara Kencong Branch) - Vadilah, Lia Putri; Sulistyo, Agung Budi; Cholifah, Umi (IJABAH: Indonesian Journal of Sharia Economics, Business, and Halal Studies, 2024)
This research aims to explore more deeply the suitability of the application of the Rahn Tasjily concept in the BMT UGTN Capem Kencong with the DSN-MUI Fatwa and explore and analyze the application of Sharia Marketing Mix in the Rahn Tasjily contract in an effort to increase the number of members in the BMT UGTN Kencong sub-branch. This type of research uses a descriptive qualitative approach. Researchers used primary data obtained through interviews, observation and documentation. Data validity analysis uses triangulation techniques. The results of the research concluded that the concept of implementing the Rahn Tasjily contract at the BMT UGT Nusantara Kencong sub-branch was in accordance with the DSN-MUI fatwa Number 68/DSN-MUI/III/2008. BMT has actually implemented indicators in the 7P sharia marketing mix which consists of Product, Price, Place, Promotion, Process, People and Physical Evidence thus increasing Rahn Tasjily's membership in 2021 to around 529 members, while in 2022 it will be 628 members. There are also findings that BMT applies the Customer Centrism theory (consumer-oriented), which means that activities prioritize customers so that members become loyal to BMT